Ximenia americana: Economic Importance, Medicinal Value, and Current Status in Ethiopia - Getachew Amare Kefelegn; Bizuayehu Desta (The Scientific World Journal)
Ximenia americana is one of the most valuable wild edible plants in the world. In different countries, it is utilized as food, medicine, an essential oil source, and the industrial component to other products. In Ethiopia, it was one of the most known and very important plants for a long period of time. It was utilized as food, a medicinal plant, and animal feed. It was also one of the most economically important and culturally valuable plants. But nowadays, it is not adequately available in the country due to deforestation problem in the years. In addition, its economic importance, current status, and medicinal roles are not well documented and understood. As for research studies, it is concluded that unless a collective effort is taken, the existence of this plant is under severe threat and needs to have some measures. This review article is aimed at addressing the abovelined topics in detail and to pinpoint and explain the importance and status of Ximenia americana.